A description of pre-hospital educator knowledge of the educational theories and methods defining simulation-based education - Van Tonder, Tanya (My University, 2020)
Background: The successful and effective use of simulation-based education (SBE) is dependent on the educator’s knowledge of educational theories and methods that underpin SBE. There is a paucity of literature that describes educator knowledge of these theories within the context of South African pre-hospital emergency medical services education. Aim: The study aimed to describe the pre-hospital educator’s knowledge of the educational theories and simulation methods defining simulation-based education. Methodology: A qualitative exploratory, descriptive research design using semi-structured face-to-face interviews were selected for this study. Nine (9) educators using SBE on the Diploma of Emergency Medical Care at a Higher Education Institution in Johannesburg were interviewed. The data were analysed using conventional content analysis. Findings: Educators using SBE on the Dip. EMC program have limited knowledge of the educational theories and methods that underpin SBE. The approach educator’s use is based on their own previous educational experiences as they have limited formal educational training. Components of simulation, such as debriefing and developing the complexity of scenarios in simulation are not fully considered by the educators who have very limited knowledge of their implications in SBE. Recommendations: Formal education training which includes educational theories and simulation methods that underpin SBE, should be made available to all educators using SBE in their teaching environment. Formal simulation education must include SBE frameworks and debriefing frameworks to guide and develop the educator’s SBE practices to ensure students learning with simulation is optimum.
A research report submitted in partial fulfillment of the requirements for the degree of Master of Health Science in Education to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, 2020